THE EFFECT OF GDRP, MINIMUM WAGE, OPEN UNEMPLOYMENT RATE, HDI ON EAST JAVA LABOR ABSORPTION 2017-2022 - Anma Dias Vidiana; Eni Setyowati (Universitas Putera Batam, 2023)
The research aims to determine the effect of GRDP, District/City Minimum Wage (UMK), Open Unemployment Rate (TPT), Human Development Index (IPM), on Labor Absorption in East Java Province in 2017-2021. The dependent variable data is employment, while UMK, TPT, HDI are independent variables sourced from the Central Bureau of Statistics of East Java Province. This study uses panel data, namely 38 district/city sectors in East Java. The estimation used is the Fixed Effect Model with analysis used to find the effect of several dependent variables on the independent variable. The results of the study show that partially GRDP has a negative and insignificant effect on employment in East Java Province, the Open Unemployment Rate (TPT) has a negative and significant effect on employment absorption in East Java Province, UMK has a negative and insignificant effect on employment working in East Java Province. Meanwhile, the HDI has a positive and significant effect on employment in East Java Province.